Usefulness of seaweeds for bioremediation of nutrient load in re-circulatory aquaculture system - Hayin Tamut (KUFOS, 2019)
Abstract- The present study attempted to explain use of three seaweeds (C. taxifolia, C. scalpelliformis and D. dichotoma) as bioremediation of fish effluent from fish culture unit in RAS system under transparent poly house. Water quality parameters along with nutrient parameters such as Total ammonia nitrogen, nitrite-N, nitrate-N, phosphate and silicate were monitored at regular intervals. Water quality parameters were did not vary much. The concentration of TAN in the fish culture unit was showed almost similar trend throughout the period of the experiment. Whereas, in treatments (I, II and III) with seaweeds the TAN values were showed a declining trend with increasing DOC, Higher values were recorded in all treatments only during the initial phase of the experiment (up to 15 DOC) and later drastically reduced below the optimum level. Nitrite-N concentration in the fish culture unit and all treatments was showing a higher value only in the initial day of culture than the optimum level. Nitrate-N concentration in the fish culture unit was showing a higher value than the optimum level only in zero DOC. whereas, in all treatments, nitrate–N higher values were recorded only well below the ideal concentrations. Phosphate levels were recorded higher only in fish culture unit during the initial days. In the case of silicate content in both fish culture unit and all treatments were ranged only below the optimum level. Nitrogenous compounds were found to be in a higher concentration fish tank were effectively removed by different seaweeds, where C. taxifolia is greater ability to removed nutrient load as compare to both C. scalpelliformis and D. dichotoma. The increase in biomass of seaweeds was showed their positive role in the conversion of the nutrients. Better growth performance in terms of SGR was noticed for C. taxifolia (1.854 %) followed by D. dichotoma (1.599 %) and C. scalpelliformis (1.361 %). The cumulative growth rate was observed more in C. taxifolia with other species comparatively with smallest portion of the initial biomass.